2014
DOI: 10.1080/02640414.2014.957714
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion, team mental models, and collective efficacy: towards an integrated framework of team dynamics in sport

Abstract: A nomological network on team dynamics in sports consisting of a multi-framework perspective is introduced and tested. The aim was to explore the interrelationship among cohesion, team mental models (TMM), collective-efficacy (CE), and perceived performance potential (PPP). Three hundred and forty college-aged soccer players representing 17 different teams (8 female and 9 male) participated in the study. They responded to surveys on team cohesion, TMM, CE and PPP. Results are congruent with the theoretical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 37 publications
7
83
0
4
Order By: Relevance
“…Moreover, Morgan and colleagues argue that resilient teams are able to draw on role systems and TMMs to enable a team to organize and adapt in adverse situations (Morgan et al, 2013, 2015). The relevance of team cognition has not been overlooked by sport researchers, as there is evidence of the presence of TMMs in sport (e.g., Filho et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Morgan and colleagues argue that resilient teams are able to draw on role systems and TMMs to enable a team to organize and adapt in adverse situations (Morgan et al, 2013, 2015). The relevance of team cognition has not been overlooked by sport researchers, as there is evidence of the presence of TMMs in sport (e.g., Filho et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, as some scholars recently built a theoretical model grounded in the inverse hypothesis (i.e. togetherness is built by cohesion affecting shared understanding; see Filho, Tenenbaum, and Yang 2015), our opinion is that future studies should consider that the causality that of the team. Instead, it was proposed as a necessary uncertainty (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Both also have been shown to be related to team performance, especially in highly interdependent teams as are basketball teams (Gully, devine, and Whitney 1995;Mesmer-Magnus and deChurch 2009). The need to link both phenomena in a multiframework perspective has been recently formulated in sport (Filho, Tenenbaum, and Yang 2015), so that novel empirical investigations of togetherness within teams are needed. As scholars, we aimed to advance knowledge and methods in team functioning research and thus suggested to (a) characterise the temporal structure of these phenomena (i.e.…”
Section: Experiencing Togetherness Through Team Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, coach turnover influences team dynamics as a whole rather than as a single team attribute. Coaches who enhance collective efficacy in their team are also likely to influence other team processes, such as cohesion and shared mental models, and peer leadership (Filho, Tenenbaum, & Yang, 2014)…”
Section: Coach Turnover and Team Dynamicsmentioning
confidence: 99%